Nazwy ryb w polszczyźnie regionalnej (na podstawie danych słownikowych) - Piotrowska-Wojaczyk, Agnieszka (Slavia Occidentalis, 2017)
The article presents a history of selected regional names of fish found in lexicographic works dating from the beginning of the new Polish era till the turn of XX/XXI century. To give a clearer picture of the selected entries, they have been compared with historical sources: Słownik staropolski [Old Polish Dictionary], Słownik polszczyzny XVI wieku [Dictionary of XVI century Polish] as well as with Elektroniczny słownik języka polskiego XVII i XVIII wieku [Electronic dictionary of XVII and XVIII century Polish] available online.